Breaking the Chains of Job-Hopping: The Interplay of Job Involvement, Satisfaction, and Affective Commitment Among Millennials - Dewi, Tantri Ratna; Ekowati, Dian (Jurnal Manajemen Teori dan Terapan| Journal of Theoretical and Applied Management, 2025)
Objective: The purpose of this paper is to examine the influence of job involvement, job satisfaction, and affective commitment on job-hopping behavior, as well as the moderating effect of alternative employment opportunities on millennial employees. Design/Methods/Approach: With a quantitative approach, this paper involved 175 millennial employees in Indonesia who were determined using purposive sampling techniques and analyzed through structural equation modeling (SEM) technique. Findings: The results reveal that job involvement and affective commitment have a positive effect on employee job-hopping behavior so that millennial employees who are fully involved in work and emotionally committed are still doing job hop. Nevertheless, work satisfaction has a detrimental effect on job-hopping activity. The moderating effect of perceived alternative employment opportunities shows insignificant results between affective commitment and job-hopping behavior, meaning that employees' perceptions of getting another job are not affecting their decision to do job-hopping. Originality/Value: This study contributes to existing literature on job hopping behavior by examining the correlation of job involvement, job satisfaction, and affective commitment, using the theory of planned behavior (TPB). Unlike many other studies, this research specifically focuses on millennials, providing a fresh perspective on this well-explored demographic's working behavior. This becomes critical as millennials have become major players in job markets, globally. Practical/Policy implication: Given the results, it is recommended that the organization design practical training and development programs and provide benefits to improve employee welfare. Emotional support from supervisors as well as co-workers is also considered effective in retaining millennial employees in the workplace.